Toleransi Dalam Islam Sebagai Landasan Kerukunan Antar Umat Beragama - Tania Tania; Khairunisa Zahwa; Dina Wahyuni Lubis; Muhammad Rifai Harahap (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
Interfaith harmony is a vital pillar in maintaining social harmony within a diverse society. This article aims to examine the meaning of interfaith harmony and tolerance from an Islamic perspective, and to identify the factors that support and hinder the creation of harmony. The method used is a literature review analyzing various sources relevant to Islamic teachings on tolerance and community life. The results of the study indicate that Islamic teachings emphasize respecting and living peacefully alongside followers of other religions, as well as valuing differences. Through education, mutual cooperation, and the roles of community leaders and the government, harmony can be strengthened. However, in practice, there are often obstacles such as a lack of understanding of religious teachings, individualism, and socio-cultural influences that lead to conflicts that can spread among religious communities. Therefore, efforts are needed to strengthen the values of tolerance, religious understanding, and strong cooperation among religious adherents to create a safe, peaceful, and harmonious life.